A socio-legal study on bully among youths in Malaysia / Ashraf Azmi ...[et al.] - Azmi, Ashraf; Nik Abdullah, Nik Azila Shuhada; Azimuddin, Nawal Nadia; Mahamah Poyi, Nik Wan Nurul Ain; Rozlan, Syazwani (2010)
Stories on bully are becoming a norm in our daily lives. Almost every day, these stories on bully make up the pages of our newspapers. It has been around for as long as we can remember. These days, media has also provided extensive coverage to raise the awareness amongst the public. However, this problem still persists. This will only stagnant their growth, thus not making them capable of achieving their ultimate potential whether in schools or in their adult years. This project paper is conducted with aims to study the existing national schools' policies and its' application, to highlight any law available that governs specifically on the offence of bully and to analyze the application of the various forms of protection provided for children as included in the Child Act 2001 and the Penal Code. This research is based on qualitative methodology where besides referring to books, articles, journals as well as internet. Interviews were also conducted with several officers from various government institutions to gather all the relevant information. Questionnaires were also handed out throughout the course of our research. It is hoped that this project paper will provide a comprehensive discussion on the lacuna and loopholes in the Malaysian Legal System pertaining the issue of bully. Finally, the project paper was ended by conclusions and recommendations that could possibly be taken as effective measures to combat the rampant problem.